Evaluation of strawberry supply chain efficiency level with data envelopment analysis (DEA) model approach in Lumbung Stroberi, Pandanrejo Village, Batu City - Ningsih, Eka Indah Suprapti; Maulidah, Silvana; Haryati, Novi; Nurirrozak, Muhamad Zahran (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
Supply chain activities are one of the considerations for business actors. However, several problems within these activities lead to inefficiencies in the performance of supply chain actors. This study aimed to describe the strawberry supply chain system and analyze its efficiency level at Lumbung Stroberi, and evaluate supplier selection based on the supply chain performance efficiency results. The respondents of this study were five partner farmers who supplied Lumbung Stroberi and were interviewed directly using questionnaires. Data analysis was conducted using two methods, namely descriptive analysis and quantitative analysis using the Data Envelopment Analysis (DEA) model approach. The study’s findings revealed the occurrence of supply chain activities from suppliers to Lumbung Stroberi and the efficiency level of the strawberry supply chain, with three suppliers operating efficiently. This supplier selection based on supply chain performance efficiency results is crucial evaluation for maintaining the efficient suppliers and improving the inefficient ones.